Challenges in conducting small group sessions in pharmacology – a Caribbean perspective - Shankar, Pathiyil Ravi (Janaki Medical College Journal of Medical Science, 2018)
Background and Objectives: Offshore Caribbean medical schools (OCMS) face various challenges with regard to learning practical and prescribing skills in pharmacology. These challenges range from short curricular time, low number of faculty, problems with early clinical exposure and geographically separated clinical sites.Materials and Methods: The author highlights these challenges using his personal experience and articles from the published literature.  The search terms used were pharmacology, Caribbean, medical students, prescribing skills and medical schools.Results: Among the problems mentioned are lacunae in the teaching-learning of prescribing skills, teaching pharmacology as a discipline during a particular semester, excessive focus preparing students for licensing exams, low number of faculty, shortage of time, challenges with providing early clinical exposure, problems with assessing skills, lack of integration with essential medicines and standard treatment guidelines, among others.Conclusion: There are a number of challenges in teaching pharmacology and therapeutics in OCMS. Most schools concentrate on the theoretical aspects of pharmacology which are tested during the licensing exams.